Information System Framework for Training Teachers on Computational Thinking - Ling-Ling, Ung; Jane, Labadin; Fitri Suraya, Mohamad (UIKTEN - Association for Information Communication Technology Education and Science, Serbia, 2021)
The call for a holistic integration of computational thinking (CT) skills across all subjects in the newly revised Malaysian curriculum of 2017 has brought to attention an urgent need to prepare teachers with the new syllabus, teaching and learning (TL) tools, and techniques, to promote effective computational thinking knowledge dissemination in their daily classroom practices. However, a preliminary investigation revealed that many teachers were still unaware of the changes within the new curriculum. There was an apparent lack of understanding of computational thinking skills in general. The study intends to propose a conceptual framework to develop knowledge about computational thinking skills among Malaysian teachers, to enhance their pedagogical repertoire to include elements of computational thinking into their teaching content. The study employs mixed-method research to capture data and construct interventions. The Information Systems Design Theory (ISDT) is used to design an effective information system (IS) and set a plan for developing the conceptual framework.